CRYSTALLINE ADMIXTURES AND THEIR EFFECT ON SELECTED PROPERTIES OF CONCRETE - Jiří Pazderka (Acta Polytechnica, 2016)
There have been many experimental measurements of the waterproofing ability and durability of concrete with a crystalline admixture, but some other important properties have not been reliably tested yet. The results of the tests, carried out by the authors, showed that crystalline admixtures reduce the water vapor permeability of concrete by 16-20 %. The authors also carried out the water pressure test in different time intervals, during the initial phase of cement hydration. The test results have shown that the full waterproofing effect of concrete with a crystalline admixture is available approximately on the 12th day after the concrete creation. The crystalline admixture effect on the compressive strength of concrete was also the subject of the testing. The results have shown that the compressive strength of the concrete with a crystalline admixture (added in an amount of 2 %) and the compressive strength of the specimens from concrete without admixture were almost identical after 28 days.